Detangling Diet from Obesity Effects on the Gut Microbiome and Metabolic Parameters Using a Non-Human Primate Model. (29th May 2020) - Shively, Carol; Clear, Kenysha; Cook, Katherine
Abstract: Objectives: Poor diet and obesity often go hand-in-hand and are difficult to discern which variable is the major driver of the gut microbiome. The objective of this study was to determine the impact of obesity within dietary exposures on the gut microbiome and metabolic parameters using a non-human primate model. Methods: Female M. fasicularis monkeys were fed a Western or Mediterranean diet for 2.5 years. We performed metagenomics sequencing on fecal samples obtained at 26 months. DNA was isolated from feces using Qiagen PowerSoil DNA extraction kit and metagenomics sequencing was performed for multikingdom microbiome analysis. DEXA scans for body adiposity and metabolic profiling were measured in each subject before the end of the study. Subjects were grouped by body fat composition (Lean (≤10% body fat) or Overweight/Obese (≥20% body fat)) and the impact of diet and adiposity was determine on the gut microbiome. Gut microbiota populations were correlated with metabolic parameters. Results: Diet is the main determinant on gut microbiome α-diversity. Obesity had no significant outcome on Shannon diversity. Obesity within each dietary pattern can influence certain gut microbes. Lean Mediterranean diet-fed animals had significantly higher L. animals and C. comes that overweight animals fed the same diet. Obese Western diet-fed animals displayed elevated proportional abundance of S. infantarius and R. chanpaneliensis that lean Western diet-fed animals. Independent of adiposity, Western diet consumption lead to two distinct microbiome populations; P. copri high and P. copri low. P. copri HIGH displayed reduced α-diversity, increased abundance of other Prevotella species ( P. stercorea, P. brevis, and P. bryantii ), and increased F. prausnitzii . P. copri negatively correlated with α-diversity. P. copri LOW displayed increased proportional abundance of E. siraeum . Gut E. siraeum populations positively correlated with plasma HDL cholesterol levels. Conclusions: Our data indicates that diet is a potent regulator of the gut microbiome, while body adiposity can subtly shift specific gut microbiota taxa within subjects fed a specific dietary pattern. Moreover, our data indicates at a sub-group of metabolically healthier subjects on a Western diet characterized by low P. copri microbiota abundance. Funding Sources: NIH and DOD BCRP.